If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (((x * 4) + -12 * 4) * 2) = x Reorder the terms for easier multiplication: (((4x) + -12 * 4) * 2) = x Multiply -12 * 4 (((4x) + -48) * 2) = x Reorder the terms: ((-48 + (4x)) * 2) = x Reorder the terms for easier multiplication: (2(-48 + (4x))) = x ((-48 * 2 + (4x) * 2)) = x ((-96 + 8x)) = x (-96 + 8x) = x Remove parenthesis around (-96 + 8x) -96 + 8x = x Solving -96 + 8x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -96 + 8x + -1x = x + -1x Combine like terms: 8x + -1x = 7x -96 + 7x = x + -1x Combine like terms: x + -1x = 0 -96 + 7x = 0 Add '96' to each side of the equation. -96 + 96 + 7x = 0 + 96 Combine like terms: -96 + 96 = 0 0 + 7x = 0 + 96 7x = 0 + 96 Combine like terms: 0 + 96 = 96 7x = 96 Divide each side by '7'. x = 13.71428571 Simplifying x = 13.71428571
| 2(x-1)(x+3)-x(x+3)=84 | | 2l*w-1=A+84 | | 4=8 | | 3+y=-y | | -(8+3)-(-7y-7)=-1 | | 426=x-532 | | 2(x+3)(x-1)=84 | | 850-z=402 | | 2x(x+2)=126 | | 5x(x+2)=126 | | 432=x-85 | | 692=x-57 | | 3b^2=7b | | x^2+7x=-12 | | 6x^2+12x=0 | | x^2+12x=9 | | (((x*4)-12*90)*2)=x | | (((x*4)-11*90)*2)=x | | 8a-4a-6a-8=2a | | 6x-10x+9=99-30 | | -5-5(-6-2y)=0 | | x^2+15x+56= | | -29-11= | | -2x-y= | | 2+3-1b= | | -1b^2= | | a+b= | | 7p+5=7+6p | | 1b^2+24= | | a+b^2= | | 3v+5= | | 13x+7(-3-1)=-64 |